The effectiveness of an aerobic exercise program on some biochemical variables of young football players - ali ibrahim alfakih, mastour (sports creativity, 2025)
The nature of football performance, with its defensive and offensive duties, is a blend of varying intensity levels. The playing conditions are constantly changing, and the pace of the match is not fixed throughout its duration. This necessitates that players perform at varying speeds and intensitys according to the circumstances and situations of the game. Based on this intensity, the need for aerobic energy varies. This study aims to identify the effectiveness of an aerobic exercise program on certain biochemical variables (cholesterol concentration, triglycerides, total lipids, and glucose concentration) in young football players under 19 years of age. One of the most important findings is that the proposed aerobic exercises have a statistically significant positive effect on all biochemical variables (cholesterol concentration, triglycerides, total lipids, and glucose concentration) in the research sample.